Avaliação de metais traços e íons majoritários em águas de chuva na cidade de São Paulo Evaluation of trace metals and major ions concentrations in rainwater in downtown São Paulo city - Anna Paula Godoy Fontenele; Jairo J. Pedrotti; Adalgiza Fornaro (Química Nova, 2009)
Rainfall samples collected in the downtown area of São Paulo city, during 2003, exhibited average concentrations of cadmium, lead and copper of 1.33, 8.52 and 49.5 nmol L-1, respectively. Among the major ions, NH4+ was the predominant species followed by NO3-, SO4(2-) and Ca2+, with volume weighed mean (VWM) concentrations of 37.1, 20.1, 11.9 and 10.8 µmol L-1, respectively. All the determined species showed high inter-events variability, including free H+ ions whose VWM concentration was 4.03 µmol L-1, corresponding to a pH value of 5.39.